Utilization of Kodular for Android-Based Student Presence Application Development - Harry Witriyono; Dedy Abdullah; Nurul Ichsan (Jurnal Komputer, Informasi dan Teknologi, 2022)
One indicator of success in an educational institution is attendance. In collage the process of assessing an attendance can be recapitulated where in attendance recording is useful for student discipline assessment. This study aims to build student attendance applications by utilizing kodular in the development of android-based applications. Kodular which has provided tools to creat android applications with the concept of drag-drop block programming so that there is no need to type program code that makes it easy for users to create android applications. The use of this application uses a smart phone during the attendance process. The presence system design is made by utilizing Quick Response Code technology which will be scanned by students during lecture hours. This application is equipped with security using the GPS (Global positioning syste) feature which is useful for minimizing fraud committed by students. There is a location point that can be determined in the application so that students who do the attendance process outside the predetermined location will fail when making attendance..